Pendampingan dan Penyuluhan Layanan Restorasi (Penyelamatan Arsip) Keluarga ( Laraska) di Desa Sasak Panjang Tajur Halang Bogor - Aulia Nurdiansyah; Santi Dewiki; Herwati Dwi Utami; Efendi Wahyono; Siti Samsiyah; Dewi Maharani; Yanti Hermawati (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
The title of this community service (PKM) is Assistance and Counseling on Family Restoration (Archives Rescue) Services (LARASKA) in Sasak Panjang Tajur Halang Village, Bogor. The purpose of this PKM activity is that it is hoped that the Laraska program in Sasak Panjang Tajur Halang Village, Bogor, can be an incentive for other communities to take advantage of the LARASKA program. This program can later become a sustainable program among residents. In this LARASKA Program, several methods are used: Lecture method; discussion method; Simulation, and practice methods. There are two activities in archival restoration, namely encapsulation, and lamination. The team chose the encapsulation activity because document lamination or laminating press activities could damage documents. The writing in the document will stick to the laminating plastic. Documents such as diplomas, certificates, marriage certificates are acid free. Simple maintenance can make documents last up to 100 years without the need for lamination. If you need to do lamination, that's fine, but the team doesn't recommend lamination and if you have to do lamination, you can do lamination but not the press method, just like on the cover but don't forget to leave a little cavity for air circulation.